2019
DOI: 10.1055/s-0039-1691491
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Deprotonative Synthesis of Biarylazacyclooctynones

Abstract: Deprotonative formation of biarylazacyclooctynone (BARAC) from the corresponding enol triflate is described. The reaction furnished the azacyclooctynone within one hour at –78 °C. This process could be performed in one pot from the starting ketone to provide a range of BARAC derivatives in moderate to excellent yields. The protocol enabled the gram-scale formation of the BARAC skeleton by reducing the number of reaction steps. Furthermore, the established method was applied to the synthesis of the BARAC deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, although halogen dance reactions of thiophene, [6] pyridine, [7] and ferrocene [8] are well known, there are few examples of their successful application to other arenes [9] . Recently, much of our efforts have been devoted to extending the limited substrate scope and utilizing the hitherto unutilized arylmetal species of the halogen dance reaction of thiophene, [10a,b] azole, [10c] pyrrole, [10d–g] and benzene [10h,i] . Nevertheless, the general conditions remain underdeveloped, even for bromopyridines, which are the most investigated halogen dance reaction substrates.…”
Section: Methodsmentioning
confidence: 99%
“…However, although halogen dance reactions of thiophene, [6] pyridine, [7] and ferrocene [8] are well known, there are few examples of their successful application to other arenes [9] . Recently, much of our efforts have been devoted to extending the limited substrate scope and utilizing the hitherto unutilized arylmetal species of the halogen dance reaction of thiophene, [10a,b] azole, [10c] pyrrole, [10d–g] and benzene [10h,i] . Nevertheless, the general conditions remain underdeveloped, even for bromopyridines, which are the most investigated halogen dance reaction substrates.…”
Section: Methodsmentioning
confidence: 99%
“…[21] We initially screened Lewis acids for switching the deprotonation site and regioselectivity of the halogen dance reaction. [22] Among the Lewis acids tested, a catalytic amount (10 mol %) of BF 3 •OEt 2 unexpectedly, specifically, and dramatically facilitated the reaction, although it did not influence the migratory aptitude of the bromo group. Experimental and theoretical studies revealed that pyridinium trifluoroborate precatalyst 44 provides lithium aryltrifluoroborate 45 by deprotolithiation with LDA, catalyzing the halogen dance reaction of various 2,3-dihalopyridines (Scheme 12).…”
Section: Lithium Aryltrifluoroborate Catalystmentioning
confidence: 96%
“…The decorated 31 was subjected to oxidative cleavage with m-CPBA and then converted to the triple bond precursor TMS substituted vinyl trifluoromethanesulfonate 33, which was then cleaved using fluoride ion to generate the BARAC. In 2019, Okano et al improved Bertozzi's synthesis method (Figure 9) [39]. Instead of introducing a TMS group onto 34, the eight-membered skeleton was firstly subjected to an oxidative cleavage of an amide-ketone 35.…”
Section: Synthesis Approaches For Baracmentioning
confidence: 99%
“…However, when the final step was conducted at 0 • C or higher, only trace amount of the product was observed. In 2019, Okano et al improved Bertozzi's synthesis method (Figure 9) [39]. Instead of introducing a TMS group onto 34, the eight-membered skeleton was firstly subjected to an oxidative cleavage of an amide-ketone 35.…”
Section: Synthesis Approaches For Baracmentioning
confidence: 99%